Efektivitas Penggunaan Teknologi Informasi dalam Pengelolaan Lembaga Pendidikan Islam Berbasis Pesantren (Penelitan di SMA Informatika Nurul Bayan Cimerak) - Nendi Sahrul Mujahid (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
Information and communication technology currently has an important role in the world of education globally because developing technology has provided vast opportunities to improve educational management and learning activities in both schools and universities. The use of technology as a medium and source of information is an appropriate alternative for developing the implementation of the Islamic education management process. Therefore, the aim of this research is how effective the use of information technology is in managing Islamic education at SMA Informatika Nurul Bayan Cimerak. The type of research in this study is qualitative research with a descriptive approach that uses data collection techniques including interviews, observations, complete open and directed discussions, as well as documentation studies involving the principal, administration, teachers and school administrators at SMA Inforatik Nurul Bayan Cimerak to describe the effectiveness of using information technology in managing Islamic education at SMA Informatika Nurul Bayan Cimerak. Administrative management in providing school administration services, there are 7 areas of implementing administrative affairs, namely: student administration, personnel administration, financial administration, facilities and infrastructure administration, letters and archives administration, curriculum administration, as well as administration of school and community relations and has utilized IT in carrying out the process school management at Nurul Bayan Cimerak Informatics High School. Meanwhile, the effectiveness of the use of information technology at Nurul Bayan Cimerak Informatics High School in managing education using qualitative research is in accordance with Minister of National Education Regulation Number 24 of 2008. However, the implementation of administration by administrative staff at Nurul Bayan Cimerak Informatics High School still has several obstacles both originating from internal or external.